Regions of ilium and fibula providing clinically usable bone for mandible reconstruction: "A different approach to bone comparison". Issue 6 (17th June 2016) - Ghassemi, Alireza; Schreiber, Lovorka; Prescher, Andreas; Modabber, Ali; Nanhekhan, Lloyd
Abstract : A variety of donor sites are available for mandibular reconstruction. We present here a different way of comparing two commonly‐used bone flaps. The lengths of the usable parts in a total of 241 coxal bones, 91 mandibles and 60 fibulas were measured. The mandible was measured from condyle‐to‐condyle and the harvestable bone length (HBL) and usable (UBL) bone lengths in fibula and ilium were also measured. The bone thickness (BT) in 60 iliac crests was measured in two parallel lines from the anterior superior iliac spine (ASIS) along the iliac crest. The mandible was 32.17 mm shorter in females than in males. The total ilium UBL was 171.12 mm in females and 178.80 mm in males. The mean HBL of the fibula was 22.6 mm shorter in females than in males. However, in some fibulas in both females and males, only 4.2% and 21.1% of the HBL respectively could be used if the ultimate goal was to insert dental implants. We found significant correlations between BT and gender in both fibula and ilium ( P ≤ 0.05). The ilium offers constant BT throughout the usable bone area with a similar bone length to the fibula. In contrast, the fibula showed variable bone dimensions, so not all of it is clinically usable. This should especially be considered in females when a mandibular reconstruction is planned with the goal of occlusal rehabilitation. Clin. Anat. 29:773–778, 2016. © 2016 Wiley Periodicals, Inc.